Internet of Things-Based Infusion Monitoring System in Optimizing Nurse Performance: A Literature Review - Kumbarani, Komang Trisanthi; Arifin, Zahwa Alya; Nurhasanah, Yukeu; Raya, Nyoman Agus Jagat (Poltekkes Kemenkes Semarang, 2025)
Background: Monitoring of infusion fluid therapy is carried out continuously as an effort to prevent embolism and nosocomial phlebitis. Nurses who are less than optimal and have inadequate numbers in controlling and monitoring the infusion system mean that the infusion system for each patient cannot be controlled continuously because the workload is high and many patients have to be monitored.Purpose: This literature review discusses various Internet of Things (IoT)-based infusion monitoring device systems related to accuracy and effectiveness in optimizing nurse work performance.Methods: Several journals search databases were used, such as ProQuest, IEEE Xplore, SAGE Journals, PubMed, and ScienceDirect. Inclusion and exclusion criteria were applied using the Boolean Logic and PICOT methods. Inclusion criteria were original articles discussing IoT-based infusion monitoring, English language, and full-text articles. The exclusion criteria applied were articles in the form of reviews.Results: This literature review used 10 international journals published in 2014-2024. To assess the quality of the literature, we use the Checklist from JBI Critical Appraisal Tools. The IoT-based infusion monitoring device system is accurate and reliable for monitoring infusions. Accuracy is presented quantitatively and qualitatively. Quantitatively, it shows a range of 88%-100%. Meanwhile, qualitatively stated accuracy means that the device can count infusion drops reliably and accurately. Thus, this IoT-based infusion monitoring system can optimize nurse performance.Conclusion: Accurate and reliable IoT monitoring system devices are able to support the optimization of nurse performance by monitoring and sending signals and information to nurses as users.